A Novel Approach to Monitoring Pulmonary Congestion in Heart Failure: Initial Animal and Clinical Experiences Using Remote Dielectric Sensing Technology. Issue 3 (25th January 2013) - Amir, Offer; Rappaport, Dan; Zafrir, Barak; Abraham, William T.
<x xml:space="preserve">Abstract</x> Despite current therapies and disease management approaches, rates of heart failure (HF) rehospitalization remain high. New tools are needed to assess preclinical (asymptomatic) pulmonary congestion to enable outpatient management. Hence, a novel monitoring system based on noninvasive remote dielectric sensing (ReDS) technology was developed. Validation of the ReDS technology was conducted in preclinical and clinical studies. In a porcine HF model, acute fluid overload followed by administration of diuretics were performed. Changes in ReDS values were correlated to serial computed tomographic (CT) assessments of lung fluid concentrations. In hospitalized decompensated HF patients, changes in ReDS values were correlated to net fluid balance changes. A nearly linear pattern between the changes in ReDS and CT fluid concentration values was observed in 6 discrete experiments (Intraclass correlation=0.95). Results from 24 patients demonstrated a reduction in ReDS values of 17.53%±11% throughout hospitalization, consistent with a reduction in pulmonary congestion. This finding strongly correlated with changes in net fluid balance (Pearson correlation=0.86; 95% confidence interval, 0.68–0.94; R2=0.74). These findings suggest that ReDS technology accurately quantifies lung fluid concentration and has potential for monitoring HF patients through hospitalization and possibly at home.